2020
DOI: 10.1101/2020.03.06.981621
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CircGLCE alleviates intervertebral disc degeneration by regulating apoptosis and matrix degradation through the targeting of miR-587/STAP1

Abstract: BackgroundIntervertebral disc degeneration (IDD) can induce profound global socioeconomic burdens. Recent studies have suggested that circular RNAs might have crucial functions in the progression of IDD. The purpose of this study was to identify a specific circular RNA and to investigate its regulatory mechanism in IDD.MethodsCircGLCE was selected after microarray analyses and was further analysed by RT-qPCR and FISH. After silencing CircGLCE, its function was assessed with RT-qPCR, immunofluorescence analysis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 55 publications
0
9
1
Order By: Relevance
“…This suggests that the glycolysis in the IVD cells might be promoted by impact injury. Interestingly, although previous research suggested that intracellular ATP of NP cells might be mainly produced via mitochondrial respiration instead of glycolysis, 12,25 increased NO production detected in our study suggested that ATP production in IVD cells via mitochondrial respiration might be inhibited by impact injury. However, we did not separate the NP and AF cells when evaluating the data.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…This suggests that the glycolysis in the IVD cells might be promoted by impact injury. Interestingly, although previous research suggested that intracellular ATP of NP cells might be mainly produced via mitochondrial respiration instead of glycolysis, 12,25 increased NO production detected in our study suggested that ATP production in IVD cells via mitochondrial respiration might be inhibited by impact injury. However, we did not separate the NP and AF cells when evaluating the data.…”
Section: Discussioncontrasting
confidence: 84%
“…Immunofluorescence staining was performed according to the method previously reported. 25 After stained with DAPI, the cells were examined with a confocal microscope (A1R; Nikon, Japan) and analyzed with ImageJ software (Rawak Software, Germany).…”
Section: Immunofluorescencementioning
confidence: 99%
“…NP cells as the main components of the nucleus pulposus are responsible for the production and maintenance of extracellular matrix (ECM) containing collagen fibres and variety of proteoglycans especially aggrecan bearing compressive loads [4]. It is generally believed that IDD is partly caused due to the depletion of NP cells and degradation of ECM [5]. Reactive oxygen species resulting from Mitochondria dysfunction or inflammatory factors such as IL-1β and TNF-α tend to trigger apoptosis and disrupt the dynamic balance between ECM synthesis and degradation in NP cells [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, noncoding RNAs (ncRNAs) have drawn growing attention because of the role which they play in a spectrum of chronic degenerative diseases of the spine and joints, encompassing IDD [12][13][14][15][16], ankylosing spondylitis [17], osteoarthritis [18,19], and rheumatoid arthritis [20]. Circular RNAs (circRNAs), microRNAs (miRNAs), and long ncRNAs are the members of the family of ncRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs bind to their target mRNAs to initiate degradation or repress their translation [21].CircRNAs have been determined to be involved in multiple biological processes to mediate IDD progression, such as cell death and growth, as well as inflammatory response and ECM metabolism [12][13][14][15][16]. Furthermore, circRNAs have also been demonstrated to have the therapeutic effect on IDD model rats [14][15][16]. Mechanistically, circRNAs acts as a competitive endogenous RNA (ceRNA) to sponge miRNAs, thereby positively regulating target mRNAs expression [12].…”
Section: Introductionmentioning
confidence: 99%